Analytical Review of Life‐Cycle Environmental Impacts of Carbon Capture and Utilization Technologies. Issue 4 (5th January 2021) - Garcia‐Garcia, Guillermo; Fernandez, Marta Cruz; Armstrong, Katy; Woolass, Steven; Styring, Peter
Abstract: Carbon capture and utilization (CCU) has been proposed as a sustainable alternative to produce valuable chemicals by reducing the global warming impact and depletion of fossil resources. To guarantee that CCU processes have environmental advantages over conventional production processes, thorough and systematic environmental impact analyses must be performed. Life‐Cycle Assessment (LCA) is a robust methodology that can be used to fulfil this aim. In this context, this article aims to review the life‐cycle environmental impacts of several CCU processes, focusing on the production of methanol, methane, dimethyl ether, dimethyl carbonate, propane and propene. A systematic literature review is used to collect relevant published evidence of the environmental impacts and potential benefits. An analysis of such information shows that CCU generally provides a reduction of environmental impacts, notably global warming/climate change, compared to conventional manufacturing processes of the same product. To achieve such environmental improvements, renewable energy must be used, particularly to produce hydrogen from water electrolysis. Importantly, different methodological choices are identified that are being used in the LCA studies, making results not comparable. There is a clear need to harmonize LCA methods for the analyses of CCU systems, and more importantly, to document and justify such methodological choices in the LCA report. Abstract : Carbon capture and utilization : Capturing CO2 offers opportunities to not only reduce CO2 concentrations in the atmosphere but also to manufacture a wide range of chemicals using this molecule as raw material. The environmental impacts of such capture and utilization technologies are reviewed to identify potential environmental benefits.